Comportamento altruísta e racionalidade econômica : uma revisão teórica - Fonseca, Fernando Sérgio de Toledo (2007)
This Study aims for a theoretical review on altruist behavior. The debate considers if the altruist motivation can be incorporated to economic analysis without resorting to the standard automated self- interest choice. The emphasis falls upon enhancing studies of altruism conduct as an analysis of the economic behavior capable of integrating issues of the ethic nature and the economic rationality in the individual decision process.The exploitation on this area of economic theory has its importance based on the fact that: in society there isn't only a self interest maximization motivation which determines the behavior of the agents. There are numerous motivations that may also be altruists, which the agents take into account in their decision processes, considering that such motivations can be based in ethical and moral principles. Qualitative and analytical aspects of economic theory were adopted for the methodological construct, which was based in the review of the literature relevant to the theme. As for the results, it was verified that altruism can be admitted along a rational and instrumental approach, as long as the altruist individual takes into account the efficient utilization of the means displayed for the promotion of other's well being. Explaining the motivational reasons of the altruist action required neglecting the traditional choice theory's methodological structure, which supports itself on the self-interest thesis. However, adopting such suppositions for the economic analysis of altruism had some difficulties, since strong self-interest arguments were found. Moreover, the findings showed that altruism isn't synonymous of genuine altruism, as was thought in the beginning of this research. In fact, many convincing arguments were found relating the altruist conduct with selfishness, that is, an apparent version of altruism or a fake altruism. In short, may it be conceived as disguised selfishness or genuine altruism, the study concludes that such human conduct may fit as an economically rational behavior.